Identification and Distinction of Tenocytes and Tendon-Derived Stem Cells - Li, Yuange; Wu, Tianyi; Liu, Shen (Frontiers in Cell and Developmental Biology, 2021)
Restoring the normal structure and function of injured tendons is one of the biggest challenges in orthopedics and sports medicine department. The discovery of tendon-derived stem cells provides a new perspective to treat tendon injuries, which is expected to be an ideal seed cell to promote tendon repair and regeneration. Due to the lack of specific markers, the identification of tenocytes and TDSCs has not been conclusive in the in vitro study of tendons. Due to the similar morphology of tendon derived cells, the comparison and identification of tenocytes and TDSCs are also blank, which causes some obstacles to the in vitro study of tendon. In this review, the characteristics of tenocytes and TDSCs are summarized and compared based on some existing research results (mainly in terms of biomarkers), and a potential marker selection for identification is suggested. It is of profound significance to further explore the mechanism of biomarkers in vivo and to find more specific markers.